Markets and livestock in the coming decades: Implications for smallholder highland producers - Staal, Steven J.; Jabbar, M.A. (International Centre for Integrated Mountain Development, 2000)
This paper reviews recent research, first to present a picture of coming trends in livestock product consumption and production in developing countries, in general, and second to derive some of the market implications of these for smallholders in the highlands. Evidence is also presented concerning the linkages between livestock, agricultural intensification, and markets. Finally several highland case studies are presented that show in detail some of the major market constraints facing highland livestock producers. Topics of discussion include the continuing livestock revolution, the link between livestock and people, smallholder access to markets: the example of dairy; constraints to livestock market participation: two case studies, v.z. smallholder dairy in hihgland Kenya, and smallholder dairy farming in highland Ethiopia.